Looking for answers? Westonci.ca is your go-to Q&A platform, offering quick, trustworthy responses from a community of experts. Experience the ease of finding precise answers to your questions from a knowledgeable community of experts. Get quick and reliable solutions to your questions from a community of experienced experts on our platform.
Sagot :
To solve the equation [tex]\( w(w-2)(6w+5) = 0 \)[/tex], we need to identify the values of [tex]\( w \)[/tex] that make this equation true. The product of several factors equals zero if and only if at least one of the factors is zero. Therefore, we will set each factor equal to zero and solve for [tex]\( w \)[/tex].
1. The first factor is [tex]\( w \)[/tex]:
[tex]\[ w = 0 \][/tex]
This gives us the first solution [tex]\( w = 0 \)[/tex].
2. The second factor is [tex]\( w - 2 \)[/tex]:
[tex]\[ w - 2 = 0 \][/tex]
Solving for [tex]\( w \)[/tex], we get:
[tex]\[ w = 2 \][/tex]
This gives us the second solution [tex]\( w = 2 \)[/tex].
3. The third factor is [tex]\( 6w + 5 \)[/tex]:
[tex]\[ 6w + 5 = 0 \][/tex]
Solving for [tex]\( w \)[/tex], we get:
[tex]\[ 6w = -5 \implies w = -\frac{5}{6} \][/tex]
This gives us the third solution [tex]\( w = -\frac{5}{6} \)[/tex].
Thus, the complete set of solutions to the equation [tex]\( w(w-2)(6w+5) = 0 \)[/tex] is:
[tex]\[ w = 0, \quad w = 2, \quad w = -\frac{5}{6} \][/tex]
These are the values of [tex]\( w \)[/tex] that satisfy the given equation.
1. The first factor is [tex]\( w \)[/tex]:
[tex]\[ w = 0 \][/tex]
This gives us the first solution [tex]\( w = 0 \)[/tex].
2. The second factor is [tex]\( w - 2 \)[/tex]:
[tex]\[ w - 2 = 0 \][/tex]
Solving for [tex]\( w \)[/tex], we get:
[tex]\[ w = 2 \][/tex]
This gives us the second solution [tex]\( w = 2 \)[/tex].
3. The third factor is [tex]\( 6w + 5 \)[/tex]:
[tex]\[ 6w + 5 = 0 \][/tex]
Solving for [tex]\( w \)[/tex], we get:
[tex]\[ 6w = -5 \implies w = -\frac{5}{6} \][/tex]
This gives us the third solution [tex]\( w = -\frac{5}{6} \)[/tex].
Thus, the complete set of solutions to the equation [tex]\( w(w-2)(6w+5) = 0 \)[/tex] is:
[tex]\[ w = 0, \quad w = 2, \quad w = -\frac{5}{6} \][/tex]
These are the values of [tex]\( w \)[/tex] that satisfy the given equation.
Steps to solve the equation 3x=6x-2
Step 1: Subtract 6x from both sides to get x by itself.
-3x=-2
Step 2: Divide both sides by -3 to get the value of x.
Step 3: x=2/3
Step 1: Subtract 6x from both sides to get x by itself.
-3x=-2
Step 2: Divide both sides by -3 to get the value of x.
Step 3: x=2/3
Thanks for stopping by. We are committed to providing the best answers for all your questions. See you again soon. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Westonci.ca is your go-to source for reliable answers. Return soon for more expert insights.